N-Acetyl Cysteine Restores Sirtuin-6 and Decreases HMGB1 Release Following Lipopolysaccharide-Sensitized Hypoxic-Ischemic Brain Injury in Neonatal Mice - Singh-Mallah, Gagandeep; Kawamura, Takuya; Ardalan, Maryam; Chumak, Tetyana; Svedin, Pernilla; Arthur, Peter G.; James, Christopher; Hagberg, Henrik; Sandberg, Mats; Mallard, Carina (Frontiers in Cellular Neuroscience, 2021)
Inflammation and hypoxia-ischemia (HI) are important etiological factors of perinatal brain injury. However, underlying mechanisms remain unclear. Sirtuins are a family of nicotinamide adenine dinucleotide (NAD)+-dependent histone deacetylases. Sirtuin-6 is thought to regulate inflammatory and oxidative pathways, such as the extracellular release of the alarmin high mobility group box-1 (HMGB1). The expression and role of sirtuin-6 in neonatal brain injury is unknown. In a well-established model of neonatal brain injury, which encompasses inflammation (lipopolysaccharide, LPS) and hypoxia-ischemia (LPS+HI), we investigated the protein expression of sirtuin-6 and HMGB1, as well as thiol oxidation. Further, we assessed the effect of the antioxidant N-acetyl cysteine (NAC) on sirtuin-6 expression, nuclear to cytoplasmic translocation and release of HMGB1 in the brain and blood thiol oxidation after LPS+HI. We demonstrate reduced expression of sirtuin-6 and increased release of HMGB1in injured hippocampus after LPS+HI. NAC treatment restored sirtuin-6 protein levels, which was associated with reduced extracellular HMGB1 release and reduced thiol oxidation in the blood. The study suggests that early reduction in sirtuin-6 is associated with HMGB1 release, which may contribute to neonatal brain injury and that antioxidant treatment is beneficial by alleviating these injurious mechanisms.